The Role of Academic Entrepreneurship and Spin-Off Companies in the Process of Technology Transfer and Commercialisation - Irena Łącka (Journal of Entrepreneurship, Management and Innovation)

(untitled)
In developed countries, the academic entrepreneurship makes up a very important element of academic environment activities. For some time, the increase in the role of technology transfer and knowledge commercialisation has been also promoted in Poland. Strong connections between the scholarship and the economy (in the future, within the university of the third generation) have a chance to build an economy based on knowledge in our country. The flow of knowledge and the introduction of new solutions (results of scholarly research) in enterprises take place through the intermediary of various methods of transfer and commercialisation paths. Independent of the manner, each fulfils an important role in the public life and economy. This is confirmed by the experience of the States that are recognised as innovation leaders, and presented in the paper as examples of Polish scholars’ academic entrepreneurship.